Synergistic effects of estradiol and 11-ketotestosterone on vitellogenin physiology in the shortfinned eel (Anguilla australis). Issue 5 (17th January 2019) - Thomson-Laing, Georgia; Damsteegt, Erin L; Nagata, Jun; Ijiri, Shigeho; Adachi, Shinji; Todo, Takashi; Hiramatsu, Naoshi; Lokman, P Mark
Abstract: Estradiol-17β (E2 ) and 11-ketotestosterone (11KT) have been implicated in vitellogenesis and in regulating expression of the follicle-stimulating hormone receptor ( fshr ), respectively. To override the captivity-induced reproductive block in shortfinned eel, Anguilla australis, we hypothesized that in combination, 11KT and E2 would stimulate ovarian uptake of vitellogenin (Vtg). Early pubertal eels received hormone implants containing varying concentrations of E2 (0, 0.2, 2, 5 mg) with or without 11KT (1 mg). Vtg levels were determined in plasma, liver, and ovarian tissues by histological examination, qPCR, immunoblotting, or single radial immunodiffusion. The expression of gonadotropin-beta subunits and gonadotropin receptors in the pituitary and ovary, respectively, were analyzed to determine mechanisms by which steroid effects may be exerted. When administered alone, E2 increased hepatic production and plasma levels of Vtg. In contrast, 11KT decreased plasma levels of Vtg, seemingly reducing its production. Neither 11KT nor E2 could induce uptake of Vtg into oocytes, although E2 treatment appeared necessary for uptake to occur. This was the case despite 11KT dramatically increasing both oocyte size and fshr mRNA levels. Astonishingly, the uptake of Vtg was successfully induced by co-treatment with 11KT and E2, suggesting that 11KT might facilitate the incorporation of Vtg into the developing oocyte. These results highlight the potential of sex steroid co-treatment, an approach aimed at mimicking oogenesis in wild eels, to induce vitellogenesis, specifically ovarian yolk deposition, even in the absence of exogenous gonadotropin treatment. Abstract : Combined treatment with estradiol-17β and 11-ketotestosterone results in evident yolk accumulation in the shortfinned eel ovary, showing the potential of steroid co-treatment to induce vitellogenesis, even in the absence of exogenous gonadotropins.